EFFECTIVENESS OF ORAL MOTOR STIMULATION ON INCREASING THE WEIGHT OF LOW BIRTH WEIGHT INFANTS - Nur Cholila; Damayanti, Tri Yunita Fitria; Nurkhalimah, Siti (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2025)
Background: Low Birth Weight (LBW) Infants often experiences feeding difficulties due to oromotor function immaturity, which directly inhibits weight gain and prolongs hospitalization. Oral motor stimulation is a promising non-pharmacological intervention to address this issue, but quantitative evidence regarding its impact in the context of local care still needs to be strengthened. Objective: This study aims to analyze the effect of oral motor stimulation intervention on weight gain in LBW infants. Method: This study used a pre-experimental design with a one-group pre-post test design. A total of 18 LBW infants who met the inclusion criteria in the Perinatology Room of R. Ali Manshur Hospital, Tuban, received oral motor stimulation intervention for 15 minutes every day for 7 consecutive days. Weight data before and after intervention were analyzed using the Paired Samples t-Test after meeting the assumption of normality through the Shapiro-Wilk test. Results: The results showed an increase in average body weight from 2122.22 grams (SD=181.68) to 2608.33 grams (SD=88.43). There was a very significant difference in body weight with an average increase of 486.11 grams; t = -13.736; p <0.001). Conclusion: Oral motor stimulation intervention was significantly effective in increasing weight gain in LBW infants. This intervention can be an important component of nursing care to optimize growth outcomes and support readiness to go home in this vulnerable population.